Compressive behavior of circular steel tubed high-strength concrete columns with embedded steel tubes. (June 2022) - Lu, Shiwei; Wang, Jizhong; Yang, Junlong; Wang, Licheng
Abstract: This paper presents an experimental study on circular steel tubed high-strength concrete columns embedded with steel tubes under axial compression. A total of 18 columns were tested in this study to investigate several parameters covering the continuity conditions for external steel tubes, diameters of internal steel tubes, thicknesses of external and internal tubes, and the number of CFRP layers. Test results show that the strength of specimens is improved to different levels due to the discontinuous external tubes and embedded internal tubes, and a significant enhancement can be achieved in terms of ductility and residual strength. Moreover, the concrete core as well as the sandwich concrete exhibits superior compressive behavior as the internal steel tube diameter increases under a constant steel ratio. Besides, when the external tubes are wrapped with CFRP jackets, more effective confinement can be provided for the inner concrete, while the effect of the position of internal steel tubes become less obvious. Finally, several existing models are selected to predict the axial stress-strain responses of the concrete in tubed columns. It is found that only two models can provide relatively reasonable predictions for the average axial stress-strain curves of concrete, but considerable overestimations of the ultimate stress are still observed for these two models, which indicates that further investigation is needed to develop a more accurate model. Highlights: Axial compressive behavior of circular tubed high-strength concrete columns embedded with steel tubes was investigated. The test parameters including continuity conditions for external steel tubes and diameters of internal steel tubes were explored. The accuracy of existing models in predicting the axial stress-strain respones of confined concrete was evaluated.